Ross seal (Ommatophoca rossii) annual distribution, diving behaviour, breeding and moulting, off Queen Maud Land, Antarctica - Blix, Arnoldus Schytte; Nordøy, Erling S. (Polar Biology, 2007)
Six out of ten adult Ross seals that were tagged with Argos satellite-linked dive recorders off Queen Maud Land, just after the moult in February, provided data on location and diving activity throughout a year. Shortly after tagging, the animals headed 2,000 km north and stayed pelagic in the area south of the Antarctic Polar Front, until October when they went south into the pack-ice. Throughout the year they made about 100 dives a day, most to a depth of 100–300 m, the deepest dive on record being 792 m, while some dives were very shallow during their stay in the pack-ice. Most dives, outside the breeding and moulting period, lasted for 5–15 min throughout the year. This diving behaviour is consistent with feeding on mid-water fish, like Pleurogramma antarcticum, squid, and to some extent krill (Euphausia superba), when in the pack-ice, and myctophid fish and several species of squid, when in the open ocean. The nursing period was 13 days in mid-November, and moulting occurs in late January–early February, which is the period when sightings surveys for this species should be done.
Keywords: Sørishavet; marin biologi; pinnipedier; satellittsendere; seler; telemetri; zoologi

Movements and dive behaviour of two leopard seals (Hydrurga leptonyx) off Queen Maud Land, Antarctica - Nordøy, Erling S; Blix, Arnoldus Schytte (Polar Biology, 2009)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Distribution and food consumption of Ross seals (Ommatophoca rossii) and Leopard seals (Hydrurga leptonyx) - Nordøy, Erling S; Blix, Arnoldus Schytte (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; havis; marin biologi; seler; sjøis; zoologi

Changing the Look on Seals from Pole to Pole with Satellite Technology - Blix, Arnoldus Schytte; Folkow, Lars P; Nordøy, Erling S (Adaptation and Evolution in Marine Environments, Volume 2: The Impacts of Global Change on Biodiversity, 2013)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Distribution, density and abundance of Antarctic ice seals off Queen Maud Land and the eastern Weddell Sea - Gurarie, Eliezer; Bengtson, John L; Bester, Marthán N; Blix, Arnoldus Schytte; Cameron, Michael; Bornemann, Horst; Nordøy, Erling S; Plötz, Joachim; Steinhage, Daniel; Boveng, Peter (Polar Biology, 2017)
Keywords: Sørishavet; Weddellhavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr; zoologi

Tracking of marine predators to protect Southern Ocean ecosystems - Hindell, Mark A; Reisinger, Ryan R; Ropert-Coudert, Yan; Hückstädt, Luis A; Trathan, Philip N; Bornemann, Horst; Charrassin, Jean-Benoît; Chown, Steven L; Costa, Daniel P; Danis, Bruno; Lea, Mary-Anne; Thompson, David; et al. (Nature, 2020)
Southern Ocean ecosystems are under pressure from resource exploitation and climate change1,2. Mitigation requires the identification and protection of Areas of Ecological Significance (AESs), which have so far not been determined at the ocean-basin scale. Here, using assemblage-level tracking of marine predators, we identify AESs for this globally important region and assess current threats and protection levels. Integration of more than 4,000 tracks from 17 bird and mammal species reveals AESs around sub-Antarctic islands in the Atlantic and Indian Oceans and over the Antarctic continental shelf. Fishing pressure is disproportionately concentrated inside AESs, and climate change over the next century is predicted to impose pressure on these areas, particularly around the Antarctic continent. At present, 7.1% of the ocean south of 40°S is under formal protection, including 29% of the total AESs. The establishment and regular revision of networks of protection that encompass AESs are needed to provide long-term mitigation of growing pressures on Southern Ocean ecosystems.
Keywords: Sørishavet; klimaendringer; marin biologi; marine økosystemer; miljøvern; overvåking